Thursday

January 29, 2015

January 29, 2015

Posted by **saya** on Sunday, May 6, 2012 at 1:30am.

- math12 -
**Reiny**, Sunday, May 6, 2012 at 7:40amlet y = 3^x , then your equation becomes

y^2 - 4y + 3 = 0

(y-3)(y-1) = 0

y = 3 or y = 1

then

3^x = 3 ---> x = 1

3^x = 1 ---> x = 0

**Answer this Question**

**Related Questions**

Math - Solve the equation. Check for extraneous roots. 4^2x-4^x-20=0

math please - Solve 3^2x + 3^x - 21 check extraneous roots

12 U Math - Solve and check for extraneous roots. log_2x+log_2(x+2)=3 * _2 is a ...

alg2 - solve for 10/x^2-2x + 4/x = 5/x-2 3x/x+1 + 6/2x = 7/x 8(x-1)/x^2-4 = 4/x-...

Trig. - Solve. Check for extraneous solution. 6x= √20+6x

Alg 2 - Solve the equation. Check for extraneous solutions. ln x + ln(x-2) = 1

math - solve equation then check for extraneous solution please someone explain ...

Algebra - solve the eauation check for extraneous solutions. log5 x=4

algebra - what does it mean to solve and check for extraneous solutions for sqry...

algebra - Solve the equation check for extraneous solution 6|6-4 x|=8 x+4answers...